The Revival of Structuralism: The Periodic Table of Mental Science - Dolsenhe, Orogee (Journal of Scientific Exploration, 2022)
Physical science solved an age-old problem in the 19th century: what makes elements similar or dissimilar? Mendeleev generally is given credit for the discovery of the underlying structure of chemical elements, known as the periodic table. Like chemicals, qualia seem to share different relationships within a modality and between modalities. Wundt’s structuralism represents an early effort to build the structure of mind through data obtained by introspection. Unfortunately, as have many other subjects, structuralism has been victimized by behaviorism’s domination. And the cognitive revolution did not completely eliminate the unfavorable status of consciousness, thus hampering the revival of structuralism unlike many other topics in psychology. With the subject of consciousness having been just about fully sanctioned by science beginning in the early 1990s, the time has come to build the periodic table of mental science by uncovering the hidden patterns of qualia. This paper proposes four different scales of intrinsic patterns: the notion of bipolar dimension, the three complementaries, the principle of square of opposition, and the double-cone system. They are able to accommodate 15 different modalities in a systematic and unified way: chromatic, acoustic, tactile, olfactory, gustatory, exteroceptive motion, exteroceptive orientative, exteroceptive locus, proprioceptive motion, proprioceptive orientative, proprioceptive locus, magnitude, emotive, hedonistic, and predicative.